Sex-specific longitudinal association of DNA methylation with lung function. Issue 3 (5th July 2021) - Sunny, Shadia Khan; Zhang, Hongmei; Relton, Caroline L.; Ring, Susan; Kadalayil, Latha; Mzayek, Fawaz; Ewart, Susan; Holloway, John W.; Arshad, S. Hasan
Investigating whether DNA methylation (DNA-M) at an earlier age is associated with lung function at a later age and whether this relationship differs by sex could enable prediction of future lung function deficit. A training/testing-based technique was used to screen 402 714 cytosine-phosphate-guanine dinucleotide sites (CpGs) to assess the longitudinal association of blood-based DNA-M at ages 10 and 18 years with lung function at 18 and 26 years, respectively, in the Isle of Wight birth cohort (IOWBC). Multivariable linear mixed models were applied to the CpGs that passed screening. To detect differentially methylated regions (DMRs), DMR enrichment analysis was conducted. Findings were further examined in the Avon Longitudinal Study of Parents and Children (ALSPAC). Biological relevance of the identified CpGs was assessed using gene expression data. DNA-M at eight CpGs (five CpGs with forced expiratory volume in 1 s (FEV1 ) and three CpGs with FEV1 /forced vital capacity (FVC)) at an earlier age was associated with lung function at a later age regardless of sex, while at 13 CpGs (five CpGs with FVC, three with FEV1 and five with FEV1 /FVC), the associations were sex-specific (p FDR <0.05) in IOWBC, with consistent directions of association in ALSPAC (IOWBC-ALSPAC consistent CpGs). cg16582803 ( WNT10A ) and cg14083603 ( ZGPAT ) were replicated in ALSPAC for main and sex-specific effects, respectively. Among IOWBC-ALSPAC consistent CpGs, DNA-M at cg01376079 ( SSH3 ) and cg07557690 ( TGFBR3 ) was associated with gene expression both longitudinally and cross-sectionally. In total, 57 and 170 DMRs were linked to lung function longitudinally in males and females, respectively. CpGs showing longitudinal associations with lung function have the potential to serve as candidate markers in future studies on lung function deficit prediction. Population-based cohort studies show that methylated sites at an earlier age are associated with lung function at a later age, possibly sex-specifically, and detected markers could serve as candidates on lung function deficit prediction in future studies https://bit.ly/3av22Dx